Biophysical regulation of mouse embryonic stem cell fate and genomic integrity by feeder derived matrices. (March 2017) - Sthanam, Lakshmi Kavitha; Barai, Amlan; Rastogi, Anuj; Mistari, Vijay K.; Maria, Ana; Kauthale, Rahul; Gatne, Madhumanjiri; Sen, Shamik
Abstract: For maintaining pluripotency, mouse embryonic stem cells (mESCs) are typically grown on mitotically inactivated mouse embryonic fibroblasts (MEFs). While the role of MEF conditioned media (MEFCM) and leukemia inhibitory factor (LIF) in regulating mESC pluripotency has led to culturing of mESCs on LIF/MEFCM supplemented gelatin-coated substrates, the role of physical interactions between MEFs and mESCs in regulating mESC pluripotency remains to be fully understood. Here, we address this question by characterizing the physicochemical properties of MEF derived matrices (MEFDMs), and probing their role in regulating mESC fate. We show that MEFDM composition and stiffness—dictated by MEF contractility—regulates mESC pluripotency by modulating mESC contractility through integrin-mediated mechanoadaptation. While baseline mESC pluripotency is maintained at early time points, activation of mESC contractility by LPA leads to drop in pluripotency levels. In contrast, addition of blebbistatin and LIF independently increases pluripotency by suppressing mechanoadaptation, highlighting the role of mechanoadaptation in regulating pluripotency and illustrating the role of LIF as a mechano-inhibitor in mESCs. Long-term culture of mESCs on MEFDMs under LIF-free conditions triggers loss of pluripotency, and induces ligand-dependent expression of the osteogenic transcription factor Runx2. Maintenance of genomic integrity (euploidy) on MEFDMs but not on gelatin-coated substrates, combined with the ability of MEFDMs in supporting LIF-free expansion and differentiation of mESCs, illustrates the suitability of MEFDMs for clinical and regenerative medicine applications.